The practical limits of inventing traditions: the failed reinvention of the Sinjska Alka - Erozden, M. Ozan (WILEY-BLACKWELL, 2013)
The Alka is a traditional game in Croatia, held to commemorate the victory of the local warriors of the region of Cetina over the Ottoman army in 1715. The Croatian nationalist discourse of the 1990s tried to reinvent the Alka as symbol of a certain national identity, by nationalising this local event and emphasising its religious aspect. In a period of just over a decade, however, the project of reinventing the Alka has failed completely. This paper analyses the reinvention of the Alka and its failure in order to argue that concrete cases of invented tradition are context dependent and may encounter practical limits.
Keywords: invention of tradition; former Yugoslavia; Croatia; nationalist discourse; national identity; Ethnic Studies; History; Government & Law; Sociology